2014
DOI: 10.1158/1078-0432.ccr-14-0011
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: CD44 Expression Denotes a Subpopulation of Gastric Cancer Cells in Which Hedgehog Signaling Promotes Chemotherapy Resistance

Abstract: Purpose Gastric cancers (GC) may harbor a small subset of cells with cancer stem cell (CSC) properties including chemotherapy (CT) resistance. The Hedgehog (HH) pathway is a key developmental pathway that can be subverted by CSCs during tumorigenesis. Here we examine the role of HH signaling in CD44(+) GC cells. Experimental Design GC cell lines, tumor xenografts, and patient tumors were examined. Results GC cell lines AGS, MKN-45, and NCI-N87 grown as spheroids or sorted for CD44(+) were found to have upr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(175 citation statements)
references
References 36 publications
3
169
1
Order By: Relevance
“…Preclinical studies suggest that gastric tumors expressing the CSC marker CD44 are associated with up‐regulation of the Hedgehog pathway and with a worse outcome 50. A biomarker study of tumor samples from a phase 2 study with vismodegib plus FOLFOX in gastric cancer confirmed these findings 38. Further study of phase 2 tumor samples revealed that, when tumors were selected for positive CD44 expression, the combination of vismodegib and FOLFOX produced increased activity over FOLFOX alone 38.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Preclinical studies suggest that gastric tumors expressing the CSC marker CD44 are associated with up‐regulation of the Hedgehog pathway and with a worse outcome 50. A biomarker study of tumor samples from a phase 2 study with vismodegib plus FOLFOX in gastric cancer confirmed these findings 38. Further study of phase 2 tumor samples revealed that, when tumors were selected for positive CD44 expression, the combination of vismodegib and FOLFOX produced increased activity over FOLFOX alone 38.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, CD44 is expressed in up to 80% of primary gastric cancer resection specimens and is associated with more advanced clinicopathologic features and a poorer prognosis 21. CD44 expression also denotes a subpopulation of gastric cancer cells in which Hedgehog signaling pathway proteins are up‐regulated and also promote chemotherapy resistance and thus a poorer prognosis 21, 38. A variant of CD44 (CD44v8‐10) was identified as the predominant CD44 variant expressed in gastric cancer cells and contributes to tumor initiation, possibly through enhancing oxidative stress defense 39.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD44(+) cells sorted from gastric cancer cell lines that were resistant to 5-Fu and cisplatin, had significantly more malignant properties, and had up-regulation of hedgehog pathway proteins. Moreover, hedgehog signaling inhibitor, vismodegib, can reverse chemotherapy resistance in CD44(+) cells [76]. Based on these and other studies, CSC-targeted treatment approaches appear to be promising to overcome drug resistance.…”
Section: Cancer Stem Cellsmentioning
confidence: 94%
“…Indeed, there is evidence that CD44v8-10 stabilizes the cystine-glutamate transporter subunit xCT and promotes the synthesis of glutathione, thereby protecting cancer cells from reactive oxygen species [70]. Depletion of the expression of CD44 leads to a decrease in the tumorigenicity of cancer cell lines [50], and Yoon et al demonstrated implication of the Hedgehog signaling in the maintenance, chemoresistance, and migration capacity of the GCSC CD44 + cells [74].…”
Section: Phenotypic Characterization Of Gastric Cancer Stem Cellsmentioning
confidence: 99%